THE INFLUENCE OF ENGLISH LEARNING MOTIVATION TOWARDS TOEFL ABILITY OF D.III AERONAUTICAL INFORMATION SERVICE CADETS IN CASEA OF MAKASSAR - Aulia Sri Megawati (Teaching English as a Foreign Language Overseas Journal, 2020)
This research is aimed to know the Influence of Internal and External Motivation cadets’ English Learning towards TOEFL Ability. This research forms used the descriptive method that the data taken from several interview and questioning and then in order to transcription form. From the results of the research, there is a significant influence English learning motivation towards TOEFL ability D.III Aeronautical Information Service cadets of Civil Aviation Safety and Engineering Academy Makassar.